KETAHANAN TERIMBAS TANAMAN CABAI MERAH TERHADAP PENYAKIT ANTRAKNOSA MELALUI INDUSER MIKORIZA INDIGENUS (Induce Resistance Of Red Chili Plant To The Anthracnose Disease By Means Of Inducer Indigenous Mycorrhiza) - yani, R. B., Mul (Universitas Palangka Raya, 2016)
ABSTRACTThe high intensity of anthracnose disease in the peat swamp area in Palangka Raya has consequentlyforced the farmers to expend higher costs for controlling and coping the disease using syntheticfungicides. The aim of this study was to investigate the role of indigenous mycorrhiza on the induceresistance structural and chemical resistance of red chili plant and to reduce the intensity ofanthracnose disease. This study was performed by using a randomized complete design method, whichwas arranged into two treatment groups in three independent repeats. The treatment factors wereclassified as follows: 1) the application of indigenous mycorrhiza (M), which was divided into twosubgroups: M0 (without mycorrhiza) and M1 (with mycorrhiza); and 2) the different doses of weed ash(A), which consisted of A0 (without ash), A1 (with 200 g of ash), A2 (with 250 g of ash), and A3 (with300 g of ash). Plants without mycorrhiza and without ash administration served as controls. The resultof this study showed that the usage of mycorrhiza with 250 g of ash per plant could reduce 49.2% ofanthracnose disease intensity, increase total phenol level amount 68,4% and the thickness of the fruitcuticle amount 49,8% compared to control groups. In conclusion, the application of mycorrhiza isbeneficial to induce resistance the total phenol level and fruit cuticle thickness; therefore itsubsequently might increase the resistance of the plant to the anthracnose disease.Keywords :indigenous mycorrhiza, inducer, induce resistance, anthracnose disease